Uma contribuição ao estudo da Ética em Lukács - Taufer, Felipe (My University, 2019)
It is a master's degree dissertation whose main goal is to seek a way to answer the following question: it is possible to think about ethics without an ontology? The answer rests on a study of the György Lukács’ Ontology of Social Being. For this, is needed to reconstruct Lukács' intellectual trajectory with an attempt to respond to this question: who really was György Lukács? It is as if, in attempting to answer such a question, there are three presuppositions that constitute the intellectual evolution of Lukács, which is due to ruptures and continuities in terms of theoretical foundation. These three assumptions allow a response of the following kind to the question: Lukacs was a moral philosopher who never wrote an Ethics. In order to analysis the "labour" chapter of Ontology we can see a meta-theoretical assumption of a kind of human action social theory. It is only these assumptions that give the basis for diagnosing the genesis of essential properties in every social ontological: value and ought-be. Indeed, the genesis of these values begins, according to Lukács, through the act of “labour”. However, not all human actions are reduced schematically to the “labour” character. Therefore, in the retreat of the natural barriers end up appearing ontological properties increasingly social. Some, even, purely social. This would be the case of ethical values and of the “ought to be” in what concerned ethics in general. Founded on an ontology in which there is no antinomy between causality and teleology, nor between necessity and possibility, it can be concluded that in Lukács' Ontology there is a thesis of the no dichotomy between facts and values. In this way, it will not be unauthorized to emphasize that Lukacs's theoretical development concerns second-order reflections on ethics, that is, a meta-ethics. It follows, as will be seen, that it is impossible, in the order of Lukacsian thought, to think an ethics without a social ontology.
Trata-se de uma dissertação de mestrado cujo objetivo maior é localizar naquilo que é implícito em Para uma ontologia do ser social de György Lukács uma maneira mais ou menos satisfatória de responder à pergunta: é possível pensar uma ética sem uma ontologia? Para tanto, será útil empreender uma reconstrução da trajetória intelectual de Lukács com a finalidade de dar uma solução para o problema: quem foi, realmente, György Lukács? Ao tentar responder tal pergunta encontram-se três pressupostos que constituem a evolução intelectual de Lukács. Evolução que se dá por rupturas e continuidades em termos de fundamentação teórica. Os três pressupostos permitem uma resposta do seguinte tipo: Lukács foi um filósofo moral que nunca escreveu uma Ética. À luz disso, uma análise do capítulo “trabalho” (Arbeit), presente na Ontologia, ressalta alguns princípios metateóricos de uma teoria da ação humana tornada consciente. Não são senão estes princípios que fornecem a base do diagnóstico teórico de Lukács. Diagnóstico que insiste em argumentar que existe algo como uma gênese de propriedades essenciais no domínio de uma ontologia social: o valor e o dever-ser. Propriedades essenciais que são categorias sociais puras. É claro que a gênese dessas categorias começa, segundo Lukács, através da garantia da produção social da existência. No entanto, nem todas ações humanas são reduzidas esquematicamente ao caráter de uma ação de trabalho. Por isso, no recuo das barreiras naturais aparecem propriedades de tipo cada vez mais social. Este seria o caso do valor ético. Fundado em uma ontologia na qual não existe antinomia entre causalidade e teleologia e nem entre necessidade e possibilidade. Sendo assim, vislumbra-se, na Ontologia de Lukács, uma tese da não-existência de dicotomia entre fatos e valores. Com isso, sublinha-se que o desenvolvimento teórico de Lukács diz respeito às reflexões de segunda ordem sobre a ética, isto é, a metaética. Disso se segue que é impossível, na ordem do pensamento lukácsiano, pensar uma ética sem uma ontologia social.
Keywords: Lukacs, György, 1885-1971; Ontologia; Ética; Ontology; Ethics